2004
DOI: 10.1038/sj.thj.6200349
|View full text |Cite
|
Sign up to set email alerts
|

Outpatient-based peripheral blood stem cell transplantation for patients with multiple myeloma

Abstract: ASCT on an outpatient basis is feasible and safe in patients with MM. More than 60% of patients are manageable at home, provided that a caregiver is available.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 25 publications
0
23
1
Order By: Relevance
“…This confirms previous studies, which already highlighted that a lack of caregivers may limit the use of outpatient HSCT programs. 7,9,13 As no previous study included the patients not discharged in the outpatient arm in their analysis, we could not discuss the comparability of our results. Moreover, the control groups used in previous studies' comparisons were often subject to the following factors: patient's refusal of outpatient follow-up, insurancecompany refusal, the absence of a caregiver, living too far from the hospital and physicians' decisions that their patient should not join the program.…”
Section: Cost Categorymentioning
confidence: 75%
See 2 more Smart Citations
“…This confirms previous studies, which already highlighted that a lack of caregivers may limit the use of outpatient HSCT programs. 7,9,13 As no previous study included the patients not discharged in the outpatient arm in their analysis, we could not discuss the comparability of our results. Moreover, the control groups used in previous studies' comparisons were often subject to the following factors: patient's refusal of outpatient follow-up, insurancecompany refusal, the absence of a caregiver, living too far from the hospital and physicians' decisions that their patient should not join the program.…”
Section: Cost Categorymentioning
confidence: 75%
“…We observed a benefit of 5 days of conventional inpatient stay for the early discharge group over their inpatient peers, which is in line with studies comparable to ours. 7,22 Other reports show large differences in the readmission rate (from 8 (ref. 6) to 90% 12 ).…”
Section: Cost Categorymentioning
confidence: 99%
See 1 more Smart Citation
“…Overall, charges related to the transplant procedure were reduced by 50% over the following 2 -5 years after the implementation of the outpatient transplant program. One EDM approach was reported by Ferrara et al Preliminary findings on 28 MM patients showed feasibility and safety of the procedure without early TRM and a 36% rate of re-admission [51]. Another study from the same group reported on a series of MM patients who underwent an autograft on an outpatient program using either post-transplant single-dose PEG-Filgrastim or conventional daily G-CSF.…”
Section: Early-discharge Model (Edm)mentioning
confidence: 92%
“…The growing demand for AHPCT significantly increases waiting lists and generate concerns about the appropriate use of health care resources and patient's quality of life. Over the past years, a number of studies have investigated safety, efficacy and potential cost-advantages of reducing hospital stay for patients undergoing AHPCT [49][50][51][52][53][54][55][56][57][58][59][60]. Thus, outpatient transplant programs have been proposed for various hematological and non-hematological malignancies [61,62].…”
Section: Outpatient Care Programsmentioning
confidence: 99%